2000
DOI: 10.1097/00000542-200009000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Accuracy of Target-controlled Propofol and Sufentanil Coinfusion in Long-lasting Surgery

Abstract: This prospective study demonstrates the predictive accuracy of the pharmacokinetic model for sufentanil infusion and confirms that for propofol during long-lasting surgery using standardized rules for the management of target controlled infusion and blood loss replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Both Pandin et al . [25] and Slepchenko et al . [26] have evaluated the accuracy of a sufentanil TCI system using the pharmacokinetic parameter set developed by Gepts et al .…”
Section: Discussionmentioning
confidence: 99%
“…Both Pandin et al . [25] and Slepchenko et al . [26] have evaluated the accuracy of a sufentanil TCI system using the pharmacokinetic parameter set developed by Gepts et al .…”
Section: Discussionmentioning
confidence: 99%
“…22,23 It has been previously been recommended that the range of plasma target concentration of sufentanil should be in the range of 0.2 to 1 ng/mL. 24 Consistent with these results, we found that the hemodynamic values were remarkably reduced when 0.8 or 1.0 ng/mL of sufentanil infusion was administered compared with 0.4 or 0.6 ng/mL (P , 0.05; Fig. 1), revealing 0.8 or 1.0 ng/mL sufentanil can maintain stable hemodynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported on the performance of both anesthetics in TCI using several pharmacokinetic models 59,64 . For sufentanil, in adults [60][61][62] and in some types of cardiac surgeries 61,63 , the mean error performance was between 11% and 30%, and for overweight patients, between 18% and 29%. Target-concentrations of sufentanil used more often, in cardiac surgeries, vary between 0.4 and 2 ng.mL -1 65 , while in noncardiac surgeries they varied between 0.15 and 0.6 ng.mL -1 65 .…”
Section: Safety Margins Of a Pharmacokinetic Model For Tci Of Anesthementioning
confidence: 99%
“…Modelos de IAC para sufentanil e remifentanil já estão disponíveis no Brasil. Diversos estudos foram publicados descrevendo os desempenhos dos dois anestésicos em IAC, durante a utilização de vários modelos farmacocinéticos [59][60][61][62][63][64] . Para o sufentanil, em pacientes adultos, 60-62 e alguns em intervenção cirúrgica cardíaca 61,63 , a média da performance de erro situou-se entre 11% e 30% e para pacientes obesos ficou entre 18% e 29% 56,64 .…”
Section: Margens De Segurança De Um Modelo Farmacocinético Para Iac Dunclassified